2018
DOI: 10.1080/01658107.2017.1405995
|View full text |Cite
|
Sign up to set email alerts
|

Could Platelet Indices and Neutrophil to Lymphocyte Ratio Be New Biomarkers for Differentiation of Arteritic Anterior Ischemic Neuropathy from Non-Arteritic Type?

Abstract: The aim of this study was to assess the possible relationship between AAION (arteritic anterior ischemic optic neuropathy) and NAION (non-arteritic anterior ischemic optic neuropathy) with blood platelet parameters and NLR (neutrophil-to-lymphocyte ratio). The medical records of 12 patients with AAION, 33 patients with NAION, and 35 healthy subjects were examined. MPV, PDW, and PCT values showed marked elevation in AAION and NAION groups compared with control group. The mean NLR was statistically significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
(47 reference statements)
3
9
0
Order By: Relevance
“…In our survey, patients with NA-AION showed a significantly lower platelet count and significantly larger platelets than controls. Former investigations have reported a correlation between NA-AION and increased MPV 11 , 13 , 14 , 18 , a result consistent with our study. Furthermore, Stiebel-Kalish et al 30 , in a systematic review and meta-analysis on aspirin use after NA-AION, concluded that there is weak evidence showing a beneficial effect of acetylsalicylic acid in preventing NA-AION in the second eye.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our survey, patients with NA-AION showed a significantly lower platelet count and significantly larger platelets than controls. Former investigations have reported a correlation between NA-AION and increased MPV 11 , 13 , 14 , 18 , a result consistent with our study. Furthermore, Stiebel-Kalish et al 30 , in a systematic review and meta-analysis on aspirin use after NA-AION, concluded that there is weak evidence showing a beneficial effect of acetylsalicylic acid in preventing NA-AION in the second eye.…”
Section: Discussionsupporting
confidence: 93%
“…Systemic hypertension, diabetes mellitus, atherosclerosis, and a crowded optic disc are well-known risk factors 3 , 4 . Former reports have suggested that systemic and local inflammation may affect the pathogenesis of NA-AION, by inducing both atherosclerosis and hypercoagulability 5 - 11 . Inflammation is the result of complex interactions between the immune and inflammatory system, which includes neutrophils, macrophages, and lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…18 An elevated NLR is associated with the functional immune status of chronic inflammation, and may be an independent risk factor for diabetic peripheral neuropathy 19 and nonarteritic anterior ischemic optic neuropathy. 20 The PLR denotes the presence of inflammation in cardiovascular disease 21 and many inflammatory disease and Fig. 2.…”
Section: Discussionmentioning
confidence: 99%
“… 18 An elevated NLR is associated with the functional immune status of chronic inflammation, and may be an independent risk factor for diabetic peripheral neuropathy 19 and nonarteritic anterior ischemic optic neuropathy. 20 The PLR denotes the presence of inflammation in cardiovascular disease 21 and many inflammatory disease and cancers, such as Behçet's disease 22 and endometrial carcinoma. 23 A high neutrophil value is a marker of a nonspecific inflammatory process, while a low lymphocyte value indicates inadequate immune regulation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some studies argued that alterations in platelet function and microvascular blood flow are more important than the inflammatory reactions in the pathogenesis of NAION. However, the exact mechanism is still unclear [ 17 ]. These inflammatory markers may be used as predictive factors and new biomarkers for NAION.…”
mentioning
confidence: 99%